Critical Pedagogy for Emancipation: Perspectives and Perceptions of Teachers of English from Kerala, India—a Quantitative Study. - Jackson K David, Dr.M Poonkodi (International Journal of Advanced Science and Technology, 2020)
Critical pedagogy, focused on emancipation has been a topic of relevance in our contemporary educational scenario for a long time. However, not many attempts have been recorded regarding the factors affecting teachers’ beliefs of critical pedagogy and practice. This study is an attempt made in that direction, by developing a questionnaire to understand teachers’ perspectives about critical pedagogy and their perceptions on teaching strategies. In this quantitative study, data on teacher understandings are collected online from teachers of English who teach English to various levels—high school, higher secondary and college, in the northern part of Kerala, India. The study affirms the need for a critical pedagogy and concludes that the teacher participants, in general, understand their role as facilitators to support the emancipatory perspective of learning.